The spillover effect of outward foreign direct investment on home countries: Evidence from the United States - Jitao Tang; Rosanne Altshuler (Rutgers University, Department of Economics, 2015)
Most studies of foreign direct investment (FDI) spillovers focus on externalities of inward FDI to host country firms. However, spillovers may also be generated from outward FDI and flow to home country firms. We test for the presence of spillovers from U.S. multinational corporations to domestic U.S. firms in the same industry, downstream industries and upstream industries using firm level information from Standard and Poor's Compustat data and industry level data on U.S. outward FDI from the U.S. Bureau of Economic Analysis. We find evidence of positive and significant spillovers flowing from multinational customers to their domestic suppliers. This is consistent with most previous studies of spillovers from inward FDI and may suggest a role for domestic policies that subsidize outward FDI. We also find that the presence of beneficial spillovers depends on several firm characteristics including exporting status, size and absorptive capacity.
Keywords: 330; Foreign Direct Investment; Home Country Spillovers; Absorptive Capacity